3
$\begingroup$

I am asked to find $$ \cfrac{1}{r^2} +\cfrac{1}{s^2} +\cfrac{1}{t^2}$$ given that $r,s,t$ are the roots of $x^3-6x^2+5x-7=0$ .

So what I did was to get the polynomial whose roots are the reciprocals of $r,s,t$ ,namely $$-7x^3+5x^2-6x+1=0$$

From that, I've then used the $2^{nd}$ Newton'sum $a_ns_2+a_{n-1}s_1+2a_{n-2}=0$.

Now given that $s_1=- \cfrac{a_{2}}{a_3}$ I have in my case $s_1=\cfrac{5}{7}$ (I've turned my polynomial into a monic polynomial) .

Therefore my Newton's sum is $$s_2-\cfrac{5}{7}s_1+2\cdot\cfrac{6}{7}=0$$ $$s_2-\cfrac{5}{7}\cdot\cfrac{5}{7} +\cfrac{12}{7}=0$$ Solving for $s_2$ I get $s_2=-\cfrac{59}{49}\approx -1,204 $

Now ,I've just started studying this stuff so I am not sure I've applied it all right(the hardest part for me is to get the signs right),so I would be really grateful if someone could verify my work .

Thanks in advance.

$\endgroup$
1
  • 1
    $\begingroup$ Your method looks good... $\endgroup$
    – Macavity
    Dec 8 '15 at 11:38
4
$\begingroup$

Another way:

$$\sum\dfrac1{r^2}=\dfrac{\sum s^2t^2}{(rst)^2}$$

Now $\sum s^2t^2=(\sum st)^2-rst(r+s+t)$

Now use Vieta's formula

$\endgroup$
3
$\begingroup$

Another approach:

Equation whose roots are squares of the roots of $$f(x)=x^3-6x^2+5x-7=0$$ is

$$f(\sqrt{x})=0$$ i.e., $$x\sqrt{x}+5\sqrt{x}=6x+7$$ squaring both sides and re arranging we get $$x^3-26x^2-59x-49=0$$ and equation whose roots are reciprocals to that of above is $$49x^3+59x^2+26x-1=0$$ and whose sum of the roots is $\frac{-59}{49}$

$\endgroup$
0
1
$\begingroup$

Let $y=\dfrac1{x^2}$

$$0=x^3-6x^2+5x-7=\dfrac{x-6}y+5x-7$$

$$\iff5x-7=\dfrac{6-x}y\iff 5xy-7y=6-x$$

$$\iff x(5y+1)=7y+6\iff x=\dfrac{7y+6}{5y+1}$$

Put this value in $$0=x^3-6x^2+5x-7$$ to form a cubic equation in $y$

Now use Vieta's formula

$\endgroup$
2
  • $\begingroup$ Thanks for you answer (+1) .Is my work worth of a look at least ? $\endgroup$
    – Mr. Y
    Dec 8 '15 at 11:17
  • $\begingroup$ @Mr.Y, If I transform the equation, I should use this method. Else I will use the method in my other answer $\endgroup$ Dec 8 '15 at 11:20
1
$\begingroup$

Still another approach. We have that $$ M=\begin{pmatrix}0 & 0 & 7 \\ 1 & 0 & -5 \\ 0 & 1 & 6\end{pmatrix}$$ is the companion matrix of your polynomial, and: $$ \frac{1}{r^2}+\frac{1}{s^2}+\frac{1}{t^2}=\text{Tr}(M^{-2})=\text{Tr}\,\begin{pmatrix}0 & 7 & 42 \\ 0 & -5 & -23 \\ 1 & 6 & 31\end{pmatrix}^{-1} $$ hence: $$ \frac{1}{r^2}+\frac{1}{s^2}+\frac{1}{t^2}=\text{Tr}\,\begin{pmatrix}-\frac{17}{49} & \frac{5}{7} & 1 \\ -\frac{23}{49} & -\frac{6}{7} & 0 \\ \frac{5}{49} & \frac{1}{7} & 0\end{pmatrix} = \color{red}{-\frac{59}{49}}.$$

$\endgroup$

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.